2022
DOI: 10.3390/ijerph191912260
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Prescribing Indicators at a District Hospital in Ghana: Do We Match WHO Standards?

Abstract: (1) Background: Rational use of medicines (RUM) and their assessment are important to ensure optimal use of resources and patient care in hospitals. These assessments are essential to identifying practice gaps for quality improvement. (2) Methods: Assessment of adherence to WHO/International Network for Rational Use of Drugs core prescribing indicators among outpatients in 2021 was conducted at the University Hospital of the Kwame Nkrumah University of Science and Technology in the Ashanti Region of Ghana. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The percentage of encounters in which a patient was prescribed at least one injection in the present study was 9.9%, which is closer the value found in 2014 Burundi outpatient encounter study all ages considered (Holloway & Henry, 2014 ), was lower than the value recommended by WHO (13.4–24.1). Results were similar to those from studies conducted in India (1.98%; 0.64%), Northwest Ethiopia (9.5%), Nepal (0.6%, 4.2%), UAE (9.5%; 0.5%), Pakistan (0%), Sri Lanka (1.2%), Ghana (7%), and in Rwanda (1.2%) (Abu Farha et al, 2022 ; Amponsah et al, 2022 ; Aryal et al, 2020 ; Atal et al, 2021 ; Atif et al, 2016b ; Galappatthy et al, 2021b ; Habimana et al, 2020 ; Mandal et al, 2022 ; Rabbani et al, 2023 ; Sema et al, 2021 ; Shrestha et al, 2021 ). In contrast, the results that exceeded the WHO optimal values were revealed from Iran (24.4%), the 1995–2015 African region systematic review (25%), and Kenya (24.9%) (Ahmadi & Zarei, 2017 ; Nyabuti et al, 2020 ; Ofori-Asenso et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The percentage of encounters in which a patient was prescribed at least one injection in the present study was 9.9%, which is closer the value found in 2014 Burundi outpatient encounter study all ages considered (Holloway & Henry, 2014 ), was lower than the value recommended by WHO (13.4–24.1). Results were similar to those from studies conducted in India (1.98%; 0.64%), Northwest Ethiopia (9.5%), Nepal (0.6%, 4.2%), UAE (9.5%; 0.5%), Pakistan (0%), Sri Lanka (1.2%), Ghana (7%), and in Rwanda (1.2%) (Abu Farha et al, 2022 ; Amponsah et al, 2022 ; Aryal et al, 2020 ; Atal et al, 2021 ; Atif et al, 2016b ; Galappatthy et al, 2021b ; Habimana et al, 2020 ; Mandal et al, 2022 ; Rabbani et al, 2023 ; Sema et al, 2021 ; Shrestha et al, 2021 ). In contrast, the results that exceeded the WHO optimal values were revealed from Iran (24.4%), the 1995–2015 African region systematic review (25%), and Kenya (24.9%) (Ahmadi & Zarei, 2017 ; Nyabuti et al, 2020 ; Ofori-Asenso et al, 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…These findings were higher than the WHO optimal value (100%). Comparing these results to others from previous similar studies, lower results were found in India (15.96%), Nepal (57.7%), United Arab Emirates (UAE) (58.6%), Pakistan (56.6%), Sri Lanka (35.5%), Kenya (27.7%), Ghana (76%), Sudan (49.8%), and African region systematic review (68%) (Abdin & Mohammed, 2021 ; Amponsah et al, 2022 ; Atal et al, 2021 ; Atif et al, 2016b ; Galappatthy et al, 2021b ; Nyabuti et al, 2020 ; Ofori-Asenso et al, 2016 ; Rabbani et al, 2023 ; Shrestha et al, 2021 ). These lower results could be attributed to the non-establishment or non-enforcement of the regulatory policies.…”
Section: Discussionmentioning
confidence: 79%
“…Due to their need for multiple medications for ongoing therapy and consequent increased risk of possible drugdrug interactions, patients with the aforementioned diseases are more vulnerable to ADR. Amponsah et al [40] reported a high incidence in the number of drugs prescribed per patient encounter in Ghana, beyond the WHO optimum of less than two. To improve medication prescription and safety, HCPs must exercise vigilance such as Home Medicines Review (HMR) and prudent adoption of evidence-based recommendations for clinical practice.…”
Section: Discussionmentioning
confidence: 99%